Contributions to the morphology and histology of the reproductive system of Janolus longidentatus Gosliner (Gastropoda: Opisthobranchia - Snyman, Frank (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.